Australia : A Biography of a Nation - Knightley, Phillip (London Vintage, 2001)
Part history, part travelogue, part memoir, this book tells the inspiring story of how a one time British colony of convicts turned itself into a prosperous and confident country. This book describes Australia's journey through the eyes of ordinary people, from the trauma of the WW-I to the decline of the relationship with Britain, and more.
Include Index
Keywords: Travel -- Australia